Design, development and performance evaluation of manual planter for system of wheat intensification - KUSHWAHA, H L; DASS, ANCHAL; KHURA, TAPAN KUMAR; SAHOO, P K; SINGH, MUKESH KUMAR; MANI, INDRA (The Indian Journal of Agricultural Sciences, 2019)
System of wheat intensification (SWI), a new planting method, has shown promising results. Manual planting in SWI is cumbersome, labored and time-consuming. Hence, a manually operated planter for SWI was designed and developed at ICAR-IARI, New Delhi, for precise planting of wheat (Triticum aestivum L.) seed. Field experiment was conducted to optimize design parameters i.e. plant spacing, number of seed/hill, treated/untreated and result was compared for conventional wheat cultivation with and without SWI management during winter season of 2015-16. The estimated labour requirements for manual planting under SWI method was 4–5 times more than the traditional drilling of wheat. The bulk density, true density, 1,000 seed weight, max. and min. dimensions and sphericity of the wheat seed were computed as 768 kg/m3, 1376 kg/m3, 39.9 g, 6.0 and 2.6 mm and 3.7, respectively. Based on these physical properties of wheat seed, a vertical cell type metering unit for single-row SWI planter was designed and fabricated. The metering unit of the planter was evaluated on a sticky belt at different speeds for distribution uniformity of seed per hill. It dropped 2-seeds per hill for 56% hills (points), 3 and 1 seeds per hill in 20% hills and missed-out seeds for 4–5% hills. The developed SWI planter was evaluated at IARI-Agronomy research field and its performance was compared with manual sowing and manual SWI planting. Number of hills germinated was found to be 22–24/m2. The distribution of plant per hill was found 69% double, 23% single, 5% triple and 3% nil. Overall, germination of seed, plant growth and yield were significantly better (> 25% higher) in the plots sown by SWI planter compared to conventional wheat sowing.